Parental cyberbullying through a global lens: children's digital rights and social media policies. Issue 3 (3rd July 2021) - Alkhallouf, Atika
ABSTRACT: This commentary draws attention to parental cyberbullying, a dangerous yet normalized form of abuse whereby parents share abusive behavior online for personal gain. Parental cyberbullying raises questions about the serious gaps in social media cyberbullying and child safety policies.